VD_FINDINFO Décision / 2017 / 121 vom 22. Februar 2017 - VD Tribunal cantonal (2017)
PLAIGNANT, PARTIE À LA PROCÉDURE, LÉSÉ, AYANT DROIT ÉCONOMIQUE, SOCIÉTÉ ÉTRANGÈRE, GESTION DÉLOYALE | 104 CPP (CH), 115 CPP (CH), 118 al. 1 CPP (CH), 393 CPP (CH)